Pemodelan Sistem Informasi Geografis Untuk Analisis Kerusakan Dan Banjir Limpasan Sungai Wawar Bagian Hilir Sub Das Wawar Di Kabupaten Purworejo - Utomo, Yogi; , Dra. Alif Noor Anna, M.Si; , Drs. Yuli Priyana, M.Si (2014)
The downstream subzone Wawar in Purworejo has the potential flood of high runoff. Recorded in 2013 there has been a flood disaster that hit Purworejo that hit most downstream subzone Wawar which resulted in many farms and villages inundated. This research was conducted in the downstream part of the subzone Wawar with the aim to (1) determine agihan damage that occurs as a result of land use around the river flood runoff from the modeling results, (2) analyze the variation damage land use modeling based on a scale of flood discharge 2, 5, and 10. The method used in this study is the experimental method using plan Q2, Q5, and Q10. Rational method in determining the flood discharge. Supported by secondary data rainfall for 24 years, the main river geometry data, and Landsat 8. The unit of analysis is the use of land around the main river. Results from this study are maps agihan river runoff flood discharge plan Wawar with Q2, Q5, and Q10. Spread Wawar's river runoff flooding hit 23 villages in the downstream, the village took the village with the widest puddle. Based on the results of the calculation of Q2 amounted to 212.02 debit m3 / s, Q5 at 279.18 m3 / s and large discharge Q10 plan is for 328 m3 / s. Extensive damage to most land use is dominated by the use of irrigated land and settlements. Extensive irrigated land are flooded with an area of 107.28 ha Q2, Q5 area of 179.97 ha and 441.53 ha area Q10. Residential land area flooded with an area of 106.72 ha Q2, Q5 covering an area of 156, 93 ha, and Q10 area of 228.18 ha. Prediction flood runoff downstream subzone Wawar will hit approximately 23 villages spread lengthwise along rivers with a variety of land use fields, irrigated fields, settlements, thickets, meadows, and gardens. Keywords: Modeling, Flood, Downstream, subzone Wawar, Geographic Information System.